SUPPRESSION OF THE PATHOGEN OF FUSARIUM WILT FUSARIUM OXYSPORUM F.SP. LYCOPERSICI ON TOMATO BY INTERCROPPING WITH GARLIC - Al-Dulaimi, S. I.; Hussein, H. Z. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study aimed to investigate and evaluate the efficiency of intercropping garlic plants with tomato and their root secretions in controlling the cause of Fusarium wilt disease by using alternative methods to the use of chemical pesticides, and the experiment was carried out in the College of Agricultural Engineering Sciences/University of Baghdad. Garlic root secretions were extracted and their effectiveness in inhibiting radial growth was studied at several concentrations. The concentration of 30 µl.ml-1 showed the highest rate of inhibition, reaching 96.3%, compared to the control treatment, which amounted to 0%, and this result confirmed the ability of garlic root secretions to inhibit pathogenic fungi. The effect of planting garlic with tomatoes on plant growth-promoting rhizobacteria (PGPR) populations was also studied, and an increase was found in the numbers of these beneficial bacteria. Intercropping significantly, in contrast to monocropping, which increased by a small percentage in the fruit-setting stage and then continued to decrease in the late fruit stage. In the pot experiment, the results of using two treatments of intercropping garlic with tomato plants and watering with garlic root secretions showed a significant reduction in the percentage of infection and disease index, reaching 58.3% and 25%, respectively. The results showed the effectiveness of the treatments used in increasing the concentrations of defensive compounds such as the enzymes Peroxidase, PAL, and the content of phenols, as the FGR treatment recorded an increase in the induction and accumulation of these compounds when detected in tomato leaves, which amounted to 39 Δ absorbance.min-1.g-1, 31 nM.mi-1.g-1, and 5.47 mg of catechol.g-1, respectively.